Perencanaan dan Pendampingan Sistem Pemantauan Tanah Berbasis IoT untuk Perkebunan Tebu di Wilayah Blitar - Witra, Widyasari Puspa Permata; Anugrah, Indra Gita; Mega, Mustikaningrum; Rahmat Dwi Sutrisno (Universitas Muhammadiyah Gresik, 2025)
The application of Internet of Things (IoT) technology in the agricultural sector is a key strategy to improve efficiency, productivity, and sustainability, particularly in sugarcane farming. This community service program aimed to design and assist the implementation of a soil monitoring system based on IoT in sugarcane plantations in the Blitar region. The developed system functions to monitor soil moisture, temperature, and conditions in real-time, and presents the data through a simple dashboard accessible to farmers. The program involved mentoring activities, including requirement elicitation, training, and evaluation of training in the field. The results show improved digital literacy and analytical capacity among farmers in managing their land more efficiently. Other than that, the program also fostered the formation of a farmer-led management group that plays a crucial role in sustaining the system. Positive responses from farmers and interest in replication from neighboring farming groups indicate that appropriate, accessible technologies can empower rural agricultural communities. This program is expected to serve as a model for people-centered and sustainable technology-based agricultural transformation.